(untitled) (Marketing Journal, 2025)
This article empirically analyzes the size and share of the “shadow” and “underground” economy, which is one of the important factors influencing sustainable economic development, using the example of the regions of Uzbekistan. In the study, the GDP per ca pita indicator by region is taken as the main indicator of sustainable economic development, and the relationship between the absolute volume of the shadow and hidden economy and its share in GDP is assessed using the OLS regression model. The research res ults show that a high level of the shadow and secret economy reduces the economic efficiency of regions, negatively affects fiscal stability and investment attractiveness, and limits sustainable economic growth rates. These results confirm that reducing th e shadow economy, increasing economic transparency, and deepening institutional reforms are important conditions for sustainable development. № 1 8